The Effect Of The Implementation Of Accounting Information Systems And Work Motivation On Employee Performance (Study At The Implementation Center For Housing And Residential Area Provision In Java II) - Randi Gunawan; Gun Gunawan Rachman; Dedy Sudarmadi (PT Ilmu Data Indonesia, 2026)
The implementation of accounting information systems and work motivation can support in improving employee performance. The implementation of an effective accounting information system can support the smooth process of data processing, the delivery of accurate information, and facilitate organizational operational activities. In addition, high work motivation also plays an important role in increasing employee enthusiasm, responsibility, and productivity in carrying out their duties. Therefore, the implementation of an efficient accounting information system and high work motivation can directly improve employee performance in achieving organizational goals. Good employee performance will provide benefits to the organization, both in improving work efficiency, productivity, and the quality of services provided. This study aims to determine the effect of the implementation of accounting information systems and work motivation on employee performance at the Implementing Center for Housing and Settlement Area Provision in Java II. The research method uses a random sampling sample by distributing questionnaires to 37 respondents from a total population of 77. The data were then analyzed statistically using the Structural Equation Model method based on Partial Least Square (SEM-PLS) through SmartPLS software version 4.1.1.8. The results of this study are expected to be a solution to problems related to employee performance at the Implementation Center for Housing and Settlement Area Provision in Java II. The results of this study indicate that: (1) the application of accounting information systems has an effect on employee performance, and (2) work motivation has an effect on employee performance.